Analysis Of The Factors That Influence The Decision To Use The Shopee Application For Online Shopping Transactions - Firmansyah, Firmansyah; Setyawan, Garbada Boris; Muslikhun, Alfin (Commercium : Journal of Business and Management, 2025)
This research tries to solve problems about the decision to use the Shopee application. This research reviews why students use the Shopee application for online transactions. Factors of ease, security, and trust influence the decision to use Shopee. This research is included in descriptive quantitative where the population is 5th and 7th semester students who use Shopee in management study programs on the ITESA Muhammadiyah Semarang campus, Karya Husada University, and Pandanaran University. Random sampling determined the sample, and 100 respondents were obtained. Data processing using SPSS v.25. The results of this study state that the three variables influence the decision to use Shopee. This research implies that the decision to use Shopee is very appropriate because it is easy to use, safe when transacting, and has high trust. As the marketplace leader in Indonesia, many students certainly use Shopee as their first choice.